Selective use of adjuvant chemotherapy for rectal cancer patients with ypN0 - You, Kai-yun (Springer Berlin Heidelberg, 2014)
BACKGROUND: The administration of adjuvant chemotherapy for rectal cancer patients with ypN0 is controversial. The purposes of this study were to evaluate the role of adjuvant chemotherapy in ypN0 patients and to optimize its use for these patients. METHODS: We performed a retrospective study of 160 rectal cancer patients who had the final pathology of ypN0 between March 2003 and November 2010. Overall survival (OS), disease-free survival (DFS), local recurrence-free survival (LRFS), and distant metastasis-free survival (DMFS) were compared between patients who did and did not receive adjuvant chemotherapy. Multivariate analysis was performed to explore clinical factors significantly associated with DFS, LRFS, and DMFS. RESULTS: For ypT0–2N0 patients, the 5-year OS, DFS, LRFS, and DMFS were similar between patients who did and did not receive adjuvant chemotherapy (P > 0.05). For patients with ypT3–4N0, those who were given adjuvant chemotherapy exhibited a higher 5-year OS than those who were not (P = 0.026), with also an extended 5-year DFS (P = 0.050). Further analysis indicated that adjuvant chemotherapy could decrease the rates of distant metastases for ypT3–4N0 patients with no impact on local control. In multivariable analysis, both the final pathological stage and adjuvant chemotherapy were independent predictors of DMFS for the whole group. When stratified by pathological stage, adjuvant chemotherapy was still significantly associated with DMFS in the ypT3–4 stratum. CONCLUSIONS: Adjuvant chemotherapy may not improve survival for ypT0–2N0 patients. However, it may be clinically meaningful for ypT3–4N0 patients by decreasing rates of distant metastases. Further randomized controlled clinical trials are needed to address this problem.